InterPAD is a database of drug-drug interaction between phytochemicals and anticancer drugs - Aili Zhang; Xueni Sun; Qibiao Wu; Haiyang Jiang; Lihui Xu; Quan Gao; Zijing Yang; Sisi Zhu; Xinbing Sui (Scientific Reports)
Abstract The plant kingdom is a crucial source of potential medicines, with medicinal plants playing a significant role, they have been used to treat various diseases, including cancer. Phytochemicals have emerged as promising candidates for enhancing conventional cancer treatment strategies, particularly in addressing the persistent challenges associated with such therapies. For a long time, combined therapy has been widely adopted to overcome the limitations of monotherapies. To optimize therapeutic outcomes, it is crucial to understand the mechanisms underlying the interactions between phytochemicals and conventional drugs. Based on the above, we have developed a database named InterPAD, which serves as a valuable resource to retrieve detailed information on the interactions between phytochemicals and anticancer drugs. It offers insights into their mechanisms of action and therapeutic effects, thereby facilitating a deeper understanding of how these phytochemicals can be effectively integrated into modern cancer treatment protocols. A total of 1,055 interactions involving 331 phytochemicals and 244 anticancer drugs were meticulously reviewed and manually curated from the original publications into the InterPAD database. Additionally, InterPAD curates from 680 medicinal plants, providing detailed phytochemicals-related plant information. The database also includes 619 regulatory molecules and 74 cancer types, sourced from other databases, to elucidate cancer-specific molecular mechanism and therapeutic effects. To our knowledge, InterPAD is the first comprehensive database to investigate the synergistic or antagonistic interactions of phytochemicals with drugs across various cancer types. It uniquely highlights the biological effects of phytochemicals-based anticancer interactions through the framework of “multiple-regulatory molecules and multiple-signaling pathways”, providing insights into their molecular mechanisms. This resource serves as a valuable tool for advancing research and improving cancer treatment strategies. InterPAD is accessible at: https://bddg.hznu.edu.cn/interpad/ .